2011
DOI: 10.2147/ndt.s26672
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of treatment continuation using second-generation antipsychotics in patients with schizophrenia or schizoaffective disorder

Abstract: BackgroundEffectiveness of a drug is a key concept dependent on efficacy, safety, and tolerability. Time to discontinuation of treatment is also representative of effectiveness. We investigated differences in treatment discontinuation among newly started second-generation antipsychotics in the clinical setting.MethodsUsing a retrospective cohort study design, we screened all outpatients (n = 7936) who visited the Shioiri Mental Clinic between July 1, 2008 and June 30, 2010. We identified a cohort of patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…However, the evidence that aripiprazole is more efficacious than other antipsychotics is lacking [ 79 ]. In a comparative study looking at treatment continuation of various atypical antipsychotics, aripiprazole seemed to have lower rates of relapse; however, the study design was a large observational study, which carries a lower level of evidence and provides less convincing support [ 80 ]. In a meta-analysis of comparative trials, the overall effectiveness of aripiprazole in treating psychotic symptoms was no different than olanzapine, with similar discontinuation rates compared to all groups, although the quality of data analyzed was viewed as generally poor as many studies lacked detailed methods of randomization and blinding [ 81 ].…”
Section: Role Of Antipsychotics In Prevention Of Dspmentioning
confidence: 99%
“…However, the evidence that aripiprazole is more efficacious than other antipsychotics is lacking [ 79 ]. In a comparative study looking at treatment continuation of various atypical antipsychotics, aripiprazole seemed to have lower rates of relapse; however, the study design was a large observational study, which carries a lower level of evidence and provides less convincing support [ 80 ]. In a meta-analysis of comparative trials, the overall effectiveness of aripiprazole in treating psychotic symptoms was no different than olanzapine, with similar discontinuation rates compared to all groups, although the quality of data analyzed was viewed as generally poor as many studies lacked detailed methods of randomization and blinding [ 81 ].…”
Section: Role Of Antipsychotics In Prevention Of Dspmentioning
confidence: 99%
“…It was reported that patients with schizophrenia treated with aripiprazole (ARI), a DRD2 partial agonist (DPA), have lower rates of relapse of psychosis and treatment discontinuation compared to those treated with other antipsychotics, including several new atypical antipsychotics ( Azekawa et al., 2011 ; Gorwood, 2006 ). We demonstrated in an animal model that a chronic administration of ARI did not induce a DRD2 up-regulation or behavioral supersensitivity, whereas equivalent doses of haloperidol, a full DRD2 antagonist, induced a prominent DRD2 up-regulation and behavioral supersensitivity ( Tadokoro et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The relatively fewer metabolic side effects might be one of the reasons explaining the recent finding by Azekawa et al of a significantly longer time to discontinuation of treatment compared with olanzapine, risperidone, and blonanserin in patients with schizophrenia and schizoaffective disorder 45. This is of great relevance because nonadherence and early discontinuation of treatment can be in a causal relationship with supposed treatment resistance.…”
Section: Rationale For Aripiprazole In Treatment-resistant Schizophreniamentioning
confidence: 98%